Hubungan Pendidikan Orang Tua dan Keadaan Ekonomi Terhadap Prestasi Belajar Siswa Kelas VIII SMP Negeri 1 Klaten Tahun Ajaran 2015/2016 - Juwandari, Kurnia Indah; , Idris Harta, MA. Ph.D (2016)
ABSTRACT The purpose of this study was to determine the relationship of parent education on learning achievement in class VIII SMP N 1 Klaten 2015/2016 school year, to determine the relationship of the economic situation on the learning achievement in class VIII SMP N 1 Klaten academic year 2015/2016 and for determine the relationship of parent education and economic conditions on the learning achievement in class VIII SMP N 1 Klaten academic year 2015/2016. This type of research is the study are correlational. The study was conducted in SMP Negeri 1 Klaten. The population in this study were all students of class VIII with a number of 210 students. The sample in this study is 62 students. Data analysis techniques using multiple linear regression analysis. The results showed regression coefficient of 0.563 parental education, the coefficient is positive, it means there is a positive relationship between parental education and learning achievement. The regression coefficient economic circumstances amounting to 0,348, the coefficient is positive, it means there is a positive relationship between economic circumstances and learning achievement. Taken together education of parents (X1) and economic conditions (X2) have a significant relationship to the student achievement it is shown by the percentage of donations given parental education and economic conditions was 11.7%. Based on the results of effective contribution and relative contribution of variable data shows that the economic situation is more effective than the education of parents is the relative contribution of 57.2% and the effective contribution of 6.66%. Keywords: Parent Education. Economic circumstances. Learning achievement